Pervasive indirect genetic effects on behavioral development in polymorphic eastern mosquitofish. (25th December 2017) - Kraft, Brittany; Lemakos, Valerie A; Travis, Joseph; Hughes, Kimberly A
Abstract : "Nurture" depends on the "nature" of social partners. The behavior of a young male mosquitofish depends on genetic differences in his social partners and on his own genes. Social partners that are genetically dark or light colored affect the behavior differently. But, dark-colored males respond less to social differences than light males, and receive different behaviors from social partners. So, even apparently innate differences related to color can be caused by differences in the behavior of social partners. Abstract: The social environment can dramatically influence the development and expression of individual behavior. Indirect genetic effects (IGE) arise when variation in the social environment depends on genotypic differences among social partners. Their role in generating variation and influencing evolutionary dynamics has become increasingly recognized in recent years, but less attention has been paid to how IGE arise during development. We measured the development of IGE using a discrete natural polymorphism in male coloration and associated behaviors in eastern mosquitofish ( Gambusia holbrooki ). We observed substantial IGE and direct genetic effects on behavior. For some behaviors, IGE changed and even reversed direction over the 16 weeks of the experiment, indicating important developmental dynamics. Interaction between IGE and direct genetic effects for some behaviors suggests that melanistic males were less responsive to a genetic change in their social environment than nonmelanistic males were. Alternately, social partners might vary less in the behavior they direct toward melanistic males. Color morphs differed in mating behavior and in aggressive behavior they received from social partners, but not in direct measures of aggression. Therefore, even apparently innate differences in behavior between morphs could arise as indirect effects of differences in behavior directed toward them by social partners. These results indicate that some differences attributed to melanism in this and other species might result from color morphs experiencing different social environments. Deducing the developmental and social origins of these indirect effects is therefore critical for understanding melanism-associated behavioral variation in the many species in which it occurs.